Internet use and decision making in community-based older adults - James, Bryan D.; Boyle, Patricia A.; Yu, Lei; Bennett, David A. (Frontiers in Psychology, 2013)
Use of the internet may provide tools and resources for better decision making, yet little is known about the association of internet use with decision-making in older persons. We examined this relationship in 66190 community-dwelling older persons without dementia from the Rush Memory and Aging Project, an ongoing longitudinal study of aging. Participants were asked to report if they had access to the internet and how frequently they used the internet and email. A 12-item instrument was used to assess financial and healthcare decision making using materials designed to approximate those used in real world settings. Items were summed to yield a total decision-making score. Associations were tested via linear regression models adjusted for age, sex, race, education, and a measure of global cognitive function. Secondary models further adjusted for income, depression, loneliness, social networks, social support, chronic medical conditions, instrumental activities of daily living, life space size, and health and financial literacy. Interaction terms were used to test for effect modification. Almost 70% of participants had access to the internet, and of those with access, 55% used the internet at least several times a week. Higher frequency of internet use was associated with better financial and healthcare decision making (β=0.11, p=0.002). The association persisted in a fully adjusted model (β=0.08, p=0.024). Interaction models indicated that higher frequency of internet use attenuated the relationships of older age, poorer cognitive function, and lower levels of health and financial literacy with poorer healthcare and financial decision making. These findings indicate that internet use is associated with better health and financial decision making in older persons. Future research is required to understand whether promoting the use of the internet can produce improvements in healthcare and financial decision making.